PENGENDALIAN KUALITAS PADA PRODUKSI PAKAIAN MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS - Djabbar, Azhar Rizteki; Surachman, Surachman (Jurnal Management Risiko dan Keuangan, 2022)
The purpose of this research is to analyze the causes of product defects and the efforts to overcome and prevent the recurrence of product defects. This research using failure mode and effect analysis method with an observation approach. The data was obtained at UD Chapryo Multisarana Textile Company for 3 months from December 2021 to February 2022 in Tangerang, Banten. The results of the research show; Operational risk owned by the company Convection consists of the risk of patterning/design, grading, cutting, embroidery, sewing/union, overlay, pressing/finishing, packing. The risk factors of cutting, overlay embroidery, and sewing/union are critical risks involved in the manufacture of shirts, pants, and screen printing shirts at the company. The causes of critical risk in the company Convection are cutting not according to patterns and prints, stitches are not strong and easily come off, and there are residual threads in the production process of shirts, pants, and screen printing shirts. Risk Response Planning at the company Convection provide problem solving for product defects with: making standard operating procedures for the production of production process products, performing routine maintenance on machines, checking routine materials, evaluating materials by evaluating suppliers, improving maintenance and employee empowerment, Re-checking the methods used, and improving the work environment.